Improvement of interpersonal and intrapersonal intelligence through traditional games - Ade Ratih Pratiwi; Yulia Ayriza (Department of Psychology, Universitas Negeri Yogyakarta, 2018)
This study aims to: (1) improve interpersonal intelligence through traditional games for Kindergarten A students of RumahKu Tumbuh, (2) increase intrapersonal intelligence through traditional game on Kindergarten A students of RumahKu Tumbuh, and (3) describe the process of improving interpersonal and intrapersonal intelligence through these traditional games. This study is a classroom action research, referring a modified version of the Kemmis and Taggart model. Data were collected using observation and interviews. The findings show that there is an increase in interpersonal and intrapersonal intelligence through traditional game on kindergarten. Improved interpersonal intelligence of children overall in the pre-cycle obtained an average score of 22.59 (very low category), increased to 27.06 in cycle 1 (low category), and increased again to 34.65 with category in cycle 2. As for the increase in child intrapersonal intelligence overall score obtained in the pre-cycle average of 16.82 with a very low category, increasing to 21.35 with a low category in cycle 1 and increased again to 25.88 with category in cycle 2. The process of improving interpersonal intelligence through play action includes child benefit interact in-game, effective communication when asked and answered during play, and pursuing a strategy to win in the game, while at the intrapersonal include children express their emotions in the game, and children know their feelings by doing a question and answer session with the teachers at the end of the game.